Pelatihan Budidaya Tanaman Herbal Di Desa Puasana, Kecamatan Moramo Utara, Kabupaten Konawe Selatan, Sulawesi Tenggara - Rifa'atul Mahmudah; Muhammad Isrul; Jastria Pusmarani; Rismayanti Fauziah (Progran Studi Farmasi STIKES Mandala Waluya, 2023)
The use of natural medicine is an alternative therapy that is currently being developed and is in demand by the wider community. Several types of plants that are known to have pharmacological effects (can be used to treat diseases) are ginger, galangal, turmeric and purple buttons. These plants can easily be found in various regions in Indonesia. However, this plant is a wild plant that is underused. The aim of this community service is to carry out training in cultivating herbal plants in Pusana Village, North Moramo District, South Konawe Regency, Southeast Sulawesi. Methods used include cultivation outreach, distributing herbal plant brochures, and providing plant seeds. The results of this service activity are increasing the knowledge of the Puasana village community and planting herbal plant seeds in the TOGA garden at the Puasana village hall.